Anak dan Kejahatan (Faktor Penyebab dan Perlindungan Hukum) - Ria Juliana; Ridwan Arifin (Jurnal Selat, 2019)
The State of Indonesia has never been separated from existing regulations, given that the State of Indonesia is a rule of law and all actions taken refer to the applicable law. The problem of a law lies in the procedure for the application of the law and the implementation of the law, in legal protection for children in Indonesia, both victims and perpetrators have the right to be protected, for this reason a rule of law has been set against the child’s own misconduct applicable. Problematics of arrest and detention and punishment of crimes committed by children enactment of article 43 of Act No. 3 of 1997 which explains that child detainees are basically still in effect the provisions of the Criminal Procedure Code (KUHAP) are the loss of children's rights and protection against applicable law. The development of the rights of the child is a public concern because at this time child perseverance has spread and the application of the law continues to apply to that the rights of children must also be considered to see that children's rights must also be fought for. Above everything discussed above that neglected the rights of children and their protection was due to the lack of attention from parents and families and a small part of this resulted from an environment that was not good for the character of the child himself. To create high peace and stability then the basis of the change is parents. Improvements made to the guidance of children that are carried out fundamentally with love and love, it does not rule out the possibility of child delinquency or criminal acts that are done less, other things if the child is allowed to grow without attention then does not rule out the greater the crime that will be committed.